KEPENTINGAN STANDAR BANGUNAN HIJAU INDONESIA DAN PENGARUH PENERAPANNYA TERHADAP BIAYA PROYEK SELAMA UMUR BANGUNAN - Dusia, Enry L.; Wiyono, Edwin S.; Alifen, Ratna S.; Rahardjo, Jani (JURNAL DIMENSI UTAMA TEKNIK SIPIL, 2014)
Green building council Indonesia has been publising a green buiding standar specifications in the form of greenship rating tools which consist of six aspect: land, materials, energy, water, health and building management. This research aims to determine level of importance and implementation greenship aspects by each construction partyâs. As well to determine the effect of implementation greenship aspect towards project life cycle cost aspect. That consist of initial cost, maintenance cost, operating cost, and replacement cost. Data were obtained from questionnaires on construction parties in Jakarta and Surabaya. The data is analyzed descriptively to determine the respondent views of the greenship. Using Structural Equation Modeling to determine the relationship within implementation of greenship rating tools and project life cycle cost.Research of data analysis descriptive show thatÂ the energy aspect as the most important aspect, and health aspects as the most implemented aspect by the respondents. Data analysis Structural Equation Model show the maintenance cost are influenced by the land aspect.